British Thoracic Society study of cryptogenic fibrosing alveolitis: current presentation and initial management. Fibrosing Alveolitis Subcommittee of the Research Committee of the British Thoracic Society. Issue 1 (January 1997) - Johnston, I D; Prescott, R J; Chalmers, J C; Rudd, R M
Abstract : BACKGROUND: Mortality due to cryptogenic fibrosing alveolitis (CFA) is increasing, particularly in the elderly. Optimum management remains uncertain and previous studies of the disease have largely been from specialist centres. A national study was carried out of the presentation and initial management of CFA in the UK. METHODS: All respiratory physicians in England, Scotland and Wales were invited to enter patients with newly diagnosed CFA over a two year period. CFA was diagnosed on histological grounds or according to clinical criteria which included the absence of a defined connective tissue disorder or pneumoconiosis. Participating physicians (n = 150) completed a questionnaire at patient entry and at all subsequent follow up visits and death. RESULTS: A total of 588 patients (373 men, 63%) were studied of whom 441 (75%) were referrals from primary care. Their mean (SD) age was 67.4 (10.0) years and median duration of symptoms at presentation was 9.0 months. Clubbing was more common in men (203/373; 54%) than in women (86/ 215; 40%); 209 patients (36%) were graded as severely breathless at presentation. A history of dust exposure (organic or inorganic) was present in 274 patients (47%) of whom 87 had had some exposure to asbestos. Subjects exposed to dust were more likely to have smoked and had slightly higher mean lung volumes, but were otherwise indistinguishable from those not exposed in terms of clinical presentation, management, and outcome. Transbronchial biopsy specimens were taken in 164 patients (28%) and open lung biopsy specimens in 73 (12%), but 60% had no histological diagnostic procedure. Biopsy procedures were more likely to be performed in younger patients, those with better lung function, and those with a history of asbestos exposure. At presentation a decision not to initiate specific treatment was made in 284 cases (48%). The decision to initiate treatment was made predominantly on symptomatic grounds. Two years after the close of entry to the study 266 patients (45%) had died. CONCLUSIONS: CFA is predominantly a disease of elderly patients and has a poor prognosis. Physicians generally considered CFA to be a clinical diagnosis and did not initiate treatment in up to half of patients at presentation.